Durability of CLOSE-guided pulmonary vein isolation in persistent atrial fibrillation - First results from a prospective remapping study. (19th May 2022) - Baldinger, SH; Servatius, H; Seiler, J; Madaffari, A; Kueffer, T; Muehl, A; Asatryan, B; Haeberlin, A; Noti, F; Tanner, H; Reichlin, T; Roten, L
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The CLOSE protocol for pulmonary vein isolation (CLOSE-PVI) combines ablation index and inter-lesion distance (≤6 mm) targets. CLOSE-PVI has been shown to result in high clinical success rates. Data on durability of PVI after CLOSE-PVI mainly derive from repeat procedures in paroxysmal atrial fibrillation (AF) patients with recurrent AF. Purpose: We sought to assess the incidence of pulmonary vein (PV) reconnections during a staged redo procedure performed independently of AF recurrence 6 months after CLOSE-PVI in patients with persistent AF. Methods: In this prospective, single-center study, patients with symptomatic persistent AF (EHRA score >1) undergoing AF ablation were included. Close-PVI was performed during the index procedure. A blanking period of 3 months was applied. Seven-day Holter ECGs were performed at 3 and 6 months post ablation. All patients underwent a staged redo procedure including high-density voltage mapping of the left atrium at 6 months after the index procedure. Results: Overall, 20 patients were included (median age: 68 years [IQR 63-71]; 20% women; median duration of persistent AF: 8 months [IQR 5-15]; median LAVI 45 ml/m2 [IQR 43-53]). All PVs were successfully isolated with CLOSE-PVI during the index procedure. Four patients (20%) had AF recurrence. The redo procedure was performed after a median of 6.1 months (IQR 5.6-7.3). Of 80 PVs, 71 (89%) were still isolated. No patient had a common ostium. Reconnections were observed in 3 left superior (15%), in one left inferior (5%), in one right superior (5%) and in 4 right inferior (20%) PVs. Fourteen patients (74%) had completely isolated PVs. Two of four patients with AF recurrence (50%) and 12 of 16 patients without AF recurrence (75%) had completely isolated PVs (p=0.33). Conclusions: CLOSE-PVI achieves durable PVI after 6 months in the majority of patients with persistent AF. In half of persistent AF patients with recurrence after CLOSE-PVI, all PVs are still isolated. These patients may need adjunctive ablation.